Competitive Advantage as a Pathway to International Measurement Reporting Verification Standards - Muhammad Agung Indra Bakti; Catur Widayati (Journal of Sustainable Economic and Business, 2026)
Objectives: This study examines how green marketing strategy and industry positioning influence the implementation of international Measurement, Reporting, and Verification (MRV) standards in the aviation industry of Timor-Leste, with competitive advantage as a mediating variable. The research addresses the limited empirical understanding of how strategic orientations translate into substantive environmental compliance in developing aviation markets. Methodology: A quantitative correlational design was applied using Partial Least Squares Structural Equation Modeling. Data were collected through structured questionnaires from 110 purposively selected aviation stakeholders and analyzed to test direct and indirect relationships among variables. Findings: Green marketing strategy does not significantly affect competitive advantage or MRV implementation. Industry positioning does not directly influence MRV standards but significantly strengthens competitive advantage. Competitive advantage positively and significantly affects MRV standards and fully mediates the relationship between positioning and MRV implementation. Conclusion: The results indicate that MRV adoption in developing aviation industries depends more on internal competitive capability and operational readiness than on sustainability communication alone. Positioning contributes to compliance only when it generates tangible competitive advantage. These findings highlight the need to reframe MRV as a strategic instrument of competitiveness rather than merely a regulatory obligation.